Pulmonary fibrosis in patients with autoimmune pulmonary alveolar proteinosis: a retrospective nationwide cohort study - Yoann Guirriec; David Luque-Paz; Gontran Bernard; Axelle Mabo; Mallorie Kerjouan; Cédric Ménard; Delphine Monnier; Hilario Nunes; Yurdagül Uzunhan; Martine Reynaud-Gaubert; Julien Bermudez; Raphaël Borie; et al. (ERJ Open Research)
Background Autoimmune pulmonary alveolar proteinosis (aPAP) is a rare disease that may progress towards pulmonary fibrosis. Data about fibrosis prevalence and risk factors are lacking. Methods In this retrospective multicentre nationwide cohort, we included patients newly diagnosed with aPAP between 2008 and 2018 in France and Belgium. Data were collected from medical records using a standardised questionnaire. Results 61 patients were included in the final analysis. We identified 5 patients (8%) with fibrosis on initial computed tomography (CT) and 16 patients (26%) with fibrosis on final CT after a median time of 3.6 years. Dust exposure was associated with pulmonary fibrosis occurrence (OR 4.3; p=0.038). aPAP patients treated with whole-lung lavage, rituximab or granulocyte–monocyte colony-stimulating factor therapy did not have more fibrotic evolution than patients who did not receive these treatments (n=25 out of 45, 57% versus n=10 out of 16, 62%; p=0.69). All-cause mortality was significantly higher in fibrotic than in nonfibrotic cases (n=4 out of 16, 25% versus n=2 out of 45, 4.4%; p=0.036, respectively). Conclusion In our population, a quarter of aPAP patients progressed towards pulmonary fibrosis. Dust exposure seems to be an important factor associated with this complication. More studies are needed to analyse precisely the impact of dust exposure impact, especially silica, in patients with aPAP.